Déclin des villes moyennes et conflictualité territoriale au Maroc. Les conséquences d’une pluralisation politique inachevée ? - David Goeury; Olivier Deau (L’Année du Maghreb)
Morocco is regularly the scene of particularly strong localized mobilizations that remind us of the structural difficulties of generating development throughout the country. Today, the socio-economic indicators of many medium-sized cities reveal the lack of prospects for urban youth who suffer from a growing sense of relative deprivation. The stagnation or even economic decline of some medium-sized cities has favoured the redeployment of clientelist political networks wishing to occupy historical intermediation functions. However, while these networks hoped to renew their legitimacy by taking advantage of the process of advanced regionalisation, the intensity of the mobilisations, which were sometimes violent, were seized by the government in a context of conflict between the majority and the opposition. Governemental majority hopes to discredit local elected representatives and strengthens its influence. In the end, the dynamics of political pluralization appears to be unfinished because it renews dependency relationships between the center and the periphery without allowing the affirmation of local dynamics able to support inclusive territorial policies.